United Kingdom : Financial Sector Assessment Program-Macroprudential Institutional Framework-Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
This paper reviews the institutional framework for the conduct of macroprudential policy in the United Kingdom and the steps taken by the authorities to make the macroprudential framework operational. An effective macroprudential framework is crucial for the U.K. financial system to remain a global public good, given its size and systemic nature. The paper reviews how the institutional setup promotes the willingness to act, ability to act, effective cooperation, and accountability. A strong institutional framework is essential to ensure that macroprudential policy can work effectively. This review is also focused on the authorities' processes for monitoring systemic risk (including beyond the core financial system), data gaps, and the U.K. macroprudential toolkit.